KAEDAH KEDABITAN PERIWAYAT: KAEDAH AL-JARH WA TADHBIT - Muadilah Hs. Bunganegara; I Gusti Bagus Agung Perdana Rayyn (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
Abstract : Kedabitan is one of the requirements for categorizing a hadith, whether it is of valid, hasan or daif quality. The narrator's method of inheritance is a very important measurement tool in hadith research, especially in the aspect of the narrator's intellectual credibility. The existence of different views among hadith critic scholars in assessing the intellectual credibility of the narrator gave birth to the criteria for the narration of hadith narrators. This research focuses on redefining the understanding of